Integration of Digital Design and Artistic Stratification in a Full-Mouth Smile Rehabilitation: A case report - Tierientiev, Oleksandr Serhiovich (Global Prosperity, 2025)
Abstract. In modern dental practice, the development and application of effective methods for achieving success in comprehensive functional and aesthetic rehabilitation remains an urgent issue. In the practice of prosthetic dentistry, digital protocols are increasingly used, which helps to apply a more comprehensive and personalized approach to each patient. Patient concerns. Patient, 30 years old with complaints about the aesthetics of the anterior teeth, the presence of old restorations and secondary caries. Diagnoses: Functional diagnostics and digital smile design were performed. Interventions: 28 lithium disilicate restorations were fabricated. In the anterior area, a multilayer ceramic application was performed using Creation LS, including detailed mamelons, transition zones, and incisal effects. The posterior teeth were prepared and restored with monolithic IPS e. max CAD restorations without turning and veneering, which ensured strength and precision. The use of a virtual articulator ensured predictable occlusion and minimized intraoral adjustments. Results. In this clinical case, a comprehensive functional and aesthetic approach to rehabilitation using CAD/CAM technologies and artistic ceramic layering was presented. The uniqueness of the approach lies in the combination of digital planning with manual stratification, the use of a minimally invasive approach and highly individualized morphology of the anterior group of teeth. The protocol extends existing restorative strategies by integrating biomimetic principles with digital precision. The study achieved an effective result in terms of restoring function and aesthetic satisfaction of the patient. Conclusions. The integration of digital design with artistic ceramic layering allows for a high level of aesthetic and functional accuracy.